Perbedaan Kepatuhan Penerapan Protokol Kesehatan di Tingkat Pendidikan SLTP dan SLTA saat PTM Terbatas - Wiwin Dwi Astuti Maharjo; Yanita Trisetiyaningsih (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2022)
Background: Coronavirus originates from the latest type of virus which has now spread in the Special Region of Yogyakarta Province. From October 2021 until February 2022, confirmed cases were still increasing, therefore the government of Yogyakarta City continued to follow the rules for implementing the 50% PTMT (Limited Face-to-face Learning) by strictly maintaining the health protocols while at school. However, even though these rules were implemented, there were public and private SLTPs (Junior High School) and SLTAs (High School) with students who were non-compliant towards the health protocols, and the infrastructure available to support the health protocols at the school was inadequate. Objective: The purpose of this study is to determine the differences in compliance with the application of health protocols at SLTP and SLTA Education Level during PTMT. Method: This research design used comparative descriptive with quantitative techniques. The sampling technique used was Stratified Random Sampling. The number of respondents is 100 students, each school generates 25 respondents. Retrieval of respondent data was based on observation, demographic data, and questionnaires on compliance with the application of health protocols. The process of data analysis used the Mann-Whitney test. Results: Differences in the level of compliance obtained p-value 0.512 > 0.05, which means there is no difference in the level of compliance in public and private SLTP students. The p-value 0.274 > 0.05 means that there is no difference in the level of compliance in public and private SLTA students. The p-value of 0.464 > 0.05 means that there is no difference in the level of compliance between SLTP and SLTA students. Conclusion: There is no difference in the level of compliance in public and private SLTP students during PTMT, there is no difference in the level of compliance in public and SLTA students during PTMT, there is no difference in the level of compliance in SLTP and SLTA students during PTMT.